Shh, Respect Freedom of Speech: The Reasons Why Ngugi wa Thiong’o and Ismail Kadare Have Not Been Awarded the Nobel Prize - Llukacaj, Edona (Journal of History Culture and Art Research, 2015)
Shh, Respect Freedom of Speech: The Reasons Why Ngugi wa Thiong’o and Ismail Kadare Have Not Been Awarded the Nobel Prize Abstract The terrorist attack on the satirical French magazine, Charlie Hebdo, at the beginning of this year, intensified the unremitting debate over the right to freedom of speech and expression, as well as its limitations. Nonetheless, it was almost unanimously agreed that the human right to express personal beliefs, regardless of the fact that they could be in deep disagreement with or even insulting towards the values of certain individuals, groups, or worldviews, should be defended and promoted by the whole human community. It goes without saying that the role of intellectuals and, especially, that of the academia, in promoting tolerance, diversity, and dialogue is essential. However, this does not seem to have been one of the criteria on which the Swedish Academy based its choices, over the past years, for the awarding of the Noble Prize in Literature. Focusing on the literary contributions of Ngugi wa Thiong’o and Ismail Kadare, two repeated nominees for the Noble Prize, this paper will attempt to shed light on the reasons why these two “heroes” of free speech and representation have not been awarded the prestigious prize.